Studies on the bionomics and control of the pear bud mite Eriophyes piri, Pag. - Stubbings, W. A. K.(William Arthur Kirton) (Stellenbosch : Stellenbosch University, 2012)
Thesis (D. Sc. Agric) -- University of Stellenbosch, 1945.